한국인의 의사소통과 자기표현에 대한 연구 -칼 융의 심리학과 퇴계의 심성론을 중심으로 - 김장이; Kim, Jang-Ee (한국콘텐츠학회 논문지, 14(8), 2014)
The purpose of this study is to elucidate the emotion-understanding of Korean and thus to find out the importance of their way of self-expression by exploring the sentiment of Korean as regards their way of communications and self-expression therein. The method of this study is, being presumed the Cheong as the Korean's sentiment, to define the differences of concept between the Cheong traditionally used by them and the emotion employed in the psychology or the theory of consultation. And also, this study examines the aforementioned importance under the presumption that the Cheong in the Korean Culture makes it difficult that their emotion-understanding and self-expression to be perfect in their way of communication. In order to attain such purpose in this study, it investigates how they have seen the emotion-understanding and self-expression as to the way of communication throughout Carl G. Jung's psychology and T oegye Yi Hwang's theory of Human Mind and Nature respectively in the Occidental and Korean's Ideology. The most important thing, to be enlightened in this study, in the way of communication and self-expression are the emotion come from the big-Self(Self) in Carl G. Jung's psychology and that of the righteous sentiment from the human nature in T oegye Yi Hwang's theory of Human Mind and Nature. In conclusion, it reveals that our behavior, unvaryingly in the Orient and the Occident, is not the rational subject but the emotional one to be reacted only if our minds are attached mutually. 본 연구의 목적은, 한국인의 의사소통과 자기표현에서 한국인의 정서를 고찰하여, 그에 따른 감정을 이해하고 자기표현의 중요성을 밝히는데 있다. 연구 방법은 한국인의 정서는 정(情)이라고 보고, 우리가 통상적으로 사용하고 있는 정(情)의 개념과 상담 및 심리학에서 사용하고 있는 감정(感情) 개념에 대한 차이점을 규명하는 것이다. 아울러 한국인의 정(情) 문화가 의사소통에서 온전한 감정 이해와 자기표현을 어렵게 한다고 보고, 어떻게 감정이해를 하고 자기표현을 할 것인지를 고찰하는 것이다. 이를 위하여 본 연구는 소통에 있어서의 감정이해와 자기표현에 대하여 서양의 경우는, 칼 융 심리학을 통하여, 한국사상에서는 퇴계 심성론을 통하여 어떻게 보고 있는지 연구하였다. 본 연구를 통하여 밝히고자 한 것은, 의사소통과 자기표현에서 가장 중요한 것은 칼 융의 심리학에서는 큰 자기(Self)에서 나오는 감정이며, 퇴계 심성론에서는 성(性)에서 나오는 올바른 정(情)에 의한 감정이라는 것이다. 결론적으로 동 서양을 막론하고 우리의 행위의 주체는 이성이 아닌, 감정이라는 것과 마음이 통해야 행동으로 움직인다는 것을 알 수 있었다.